A robust cage-based framework for the highly selective purification of natural gas. Issue 69 (8th August 2019) - Hu, Falu; Huang, Pan; Di, Zhengyi; Wu, Mingyan; Jiang, Feilong; Hong, Maochun
Abstract : A robust cage-base framework exhibits highly selective purification of natural gas. Abstract : A robust microporous material (FJI-H19 ), which is constructed from distorted cuboctahedral cages and distorted octahedral cages, has been successfully synthesized.FJI-H19 possesses good thermal and water stability as well as highly selective adsorption of C3 and C4 hydrocarbons over CH4 under ambient conditions. More importantly, the high selectivities for the separation of CH4 /C3 or C4 mixtures (85/15) have not only been estimated by ideal adsorbed solution theory (IAST) but also definitely confirmed by breakthrough experiments.